Effect of protein source from Leucaena leaves on Growth Performance of Lao Local Chickens by utilization energy sources of corn meal and rice bran - INTHAVONG , Phaylin; SILIVONG, Phonevilay (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
Total 72 chickens at age 45 days, with average initial body weight of 400 g, feed until satiation, the experiment was conducted for 120 days, designed as completely randomized comparison with 3 treatments and 4 replications each, T1= RBCL0: RB 80% + C 20% + L 0%, T2= RBCL5: RB 80%+ C 15% + L 5%, T3= RBCL10: RB 80% + C 10% +L 10%. The objective was to examine feed intake, FCR, survival rate and growth performance of Lao local chicken. At the end of trial, the result shows total feed intake were statistic significantly among all groups (P<0.05), however, feed intake per body weight were not significant. High growth performance were observed by increasing level of Leucaena leaves with 10%, 5% and 0%, respectively. High growth performance and best FCR was observed in diet that combine Leucaena leaves 10%. High protein level of diet was improved to support better survival rate and FCR, meaning increase Leucaena leaves FCR was decreased.